Ragam Cendawan Mikoriza Arbuskula pada Areca di Kebun Raya Bogor - Ratu Aqila Fahriny; Agustin Wydia Gunawan (Universitas Sultan Ageng Tirtayasa, 2016)
Areca known as the pinang tree and have benefit as a powerful medicine on men. Arbuscular mycorrhizal fungi (AMF) are symbiotic on almost every root plants, but the diversity of AMF on rizosfer Areca is unknown. Therefore research on variety and colonies AMF on rizosfer Areca is needed. Soil samples of Areca were isolated and processed by wet sieving and decauting method. Root samples of Areca were stained by using trypan blue in lactoglycerol. There were 3 genera of AMF collected from Bogor Botanical Garden (4 species Acaulospora, 3 species Glomus, and 2 species Scutellospora) which is associated with 3 species of Areca. Percentage colonies of AMF rizosfer on roots Areca was counted. Areca has an intermediate type of arbuscular.